2013
DOI: 10.1007/s10811-013-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics to reveal metabolic network shifts towards lipid accumulation following nitrogen deprivation in the diatom Phaeodactylum tricornutum

Abstract: The marine diatom Phaeodactylum tricornutum is attracting considerable interest as a candidate for biofuel production due to its fast growth and high lipid content. Nitrogen deficiency can increase the lipid content in certain microalgae species, including P. tricornutum. However, the molecular basis of such changes remains unclear without analyzing metabolism at the proteomic level. We attempted to systematically analyze protein expression level changes of P. tricornutum upon N deprivation. We observed transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
71
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 30 publications
(40 reference statements)
10
71
1
3
Order By: Relevance
“…2). In good agreement, it has been previously demonstrated that a decrease in photosynthesis due to N deprivation leads to changes in metabolic pathways involved in carbon and N assimilation and metabolism [18,27,33,71]. Moreover, N shortage also results in degradation of storage compounds in some diatoms [70,72].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…2). In good agreement, it has been previously demonstrated that a decrease in photosynthesis due to N deprivation leads to changes in metabolic pathways involved in carbon and N assimilation and metabolism [18,27,33,71]. Moreover, N shortage also results in degradation of storage compounds in some diatoms [70,72].…”
Section: Discussionsupporting
confidence: 73%
“…Changes in lipid profile caused by deficiency of N in microalgae have already been reported [18,23,27,75,76]. In absence of N, a metabolic reprogramming of central carbon metabolism occurs, which diverts the carbon flow towards lipids synthesis [27,70].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Using the annotated C. reinhardtii genome (Merchant et al, 2007), the C. reinhardtii transcriptome was analyzed before and after N deprivation, which revealed multiple changes in gene expression that affect diverse parts of metabolism (Miller et al, 2010;Blaby et al, 2013;Goodenough et al, 2014;Schmollinger et al, 2014). In addition, proteomics have been used to profile the changes in protein expression during N deprivation in Phaeodactylum tricornutum (Yang et al, 2014), C. reinhardtii Longworth et al, 2012;Schmollinger et al, 2014), and Nannochloropsis oceanica (Dong et al, 2013), and metabolomics have been used to assess changes in metabolite pool sizes (Bölling and Fiehn, 2005;Lee et al, 2012). These and other studies point to wide-ranging changes in the structure and operation of the metabolic and other cellular networks.…”
mentioning
confidence: 99%
“…Under these conditions, 15 proteins in carbohydrate metabolism, stress response and defense, amino acid biosynthesis, and secondary metabolite biosynthesis were downregulated (Li et al, 2013). P. tricornutum was shown to redirect the metabolic network from carbon flux toward lipid accumulation (Yang et al, 2014). Investigation of the Synechocystis sp.…”
Section: Microalgal Systems Biologymentioning
confidence: 99%